Optimalisasi Komunikasi Publik Kepolisian melalui Aplikasi LIBAS di Polrestabes Semarang - Aryani, Sinta Dita; Khotimah, Nurul (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2025)
This study is driven by the need to enhance the effectiveness of public communication between the police and the community. The Semarang City Police (Polrestabes Semarang) developed the LIBAS application (Polisi Hebat Semarang) as a service innovation aimed at improving the speed of access to information, reporting, and police response. The research employs a qualitative descriptive approach, with data collected through observation, in-depth interviews, and documentation. The study was conducted from January to February 2025, and data were analyzed using techniques of data reduction, presentation, and conclusion drawing. The findings indicate that LIBAS functions effectively as a medium for public communication. Features such as the 001 service, SOS, incident reporting, and the panic button facilitate rapid public access to police services. The impact of LIBAS is evident in three domains: cognitive (increased public understanding of police services), affective (enhanced sense of safety and trust in the police), and behavioral (greater public initiative in reporting incidents). The data show a total of 4,233 reports: 2,466 incident reports, 1,674 reports via SOS, and 93 complaints via the panic button. Overall, the findings demonstrate that LIBAS improves public communication effectiveness and contributes to a positive image of the police. Nevertheless, the application requires further development through broader socialization and ongoing evaluation to ensure sustained service effectiveness.